Protection of Religious Sanctities and the Imperativeness to Criminalize Disrespect in International Law (Salam International Academic Journal, 2023)
The act of disrespecting sacred religious values is neither novel nor confined to any particular religion. Throughout history, instances of insulting religious sanctities—such as God, divine scriptures, prophets, religious traditions, teachings, holy sites, and rituals—have consistently evoked strong reactions from adherents. The intersection of religion with human life underscores the gravity of such disrespect, rendering insults, transgressions, and impoliteness wholly unacceptable. This research, conducted through an analytical-descriptive approach and drawing upon library sources, aims to expound upon the imperativeness of safeguarding religious sacred elements and, correspondingly, the need to criminalize their desecration within the framework of international law. Two fundamental questions guide our inquiry: Why should religious sanctities be protected? Is it necessary to criminalize insults directed at religious sanctities in international legal contexts?  The research findings underscore that while international laws recognize the right to religious freedom, they lack robust preventive mechanisms to shield religious sanctities from insult. Although freedom of speech is a fundamental right, it does not grant license to violate and demean the spiritual beliefs of others. Insults, irrespective of their context, fundamentally contravene basic human rights. Such acts not only foment animosity but also rupture the fabric of human civility, potentially inciting harmful violence.         Therefore, it is imperative to criminalize insults directed at religious sanctities becomes evident, particularly when addressed at the international level. By doing so, we acknowledge the delicate balance between freedom of expression and the imperative to protect the sacred, fostering a global environment of mutual respect and understanding.
Keywords: Religious sanctities; international law; freedom of speech; human rights, desecration